Βιβλιοκρισία:N. Zorzi – A. Berger – L. Lazzarini (eds.), I tondi di Venezia e Dumbarton Oaks. Arte e ideologia imperiale tra Bisanzio e Venezia / The Tondi in Venice and Dumbarton Oaks. Art and Imperial Ideology between Byzantium and Venice [Venetiana 21], Roma-Venezia 2019 - ΧΡΥΣΑΦΗ Ελένη (Byzantina Symmeikta, 2021)
Βιβλιοκρισία:N. Zorzi – A. Berger – L. Lazzarini (eds.), I tondi di Venezia e Dumbarton Oaks. Arte e ideologia imperiale tra Bisanzio e Venezia / The Tondi in Venice and Dumbarton Oaks. Art and Imperial Ideology between Byzantium and Venice [Venetiana 21], Roma-Venezia 2019